Struktur Komunitas dan Kelimpahan Fitoplankton serta Keterkaitannya dangan Paramater Fisik Kimia di Perairan Pesisir Banyuasin Kabupaten Banyuasin - Ridwan Arazi; Isnaini Isnaini; Fauziyah Fauziyah (Jurnal Penelitian Sains, 2019)
Changes in water quality is closely related to the abundance and phytoplankton community structure so that the presence of phytoplankton in the waters can provide information about the condition of a body of water. The purpose of this study was to evaluate the physical and chemical parameters of coastal Banyuasin, analyze the abundance and community stucture of phytoplankton abundance of phytoplankton and analyzing linkages with physico-chemical associations with chemical physics parameters in the coastal waters of South Sumatera Banyuasin was held on June 15, 2015. The determination of the research station using purposive sampling method. Phytoplankton samples taken using plankton nets (Plankton net) with a mesh size of 25 μm. Identification of phytoplankton are carried out in the laboratory by observing under a microscope and using phytoplankton identification book. The influence of enviromental parameters on the abundance of phytoplankton processed by PCA using STATISTICA software. The result showed that the phytoplankton were found composed of there classes which Bacillariophyceae, Dinophyceae and Cyanophyceae. The most common genus is Skeletonema. Value abundance of phytoplankton ranged from 78 cells/1-329 cells/1, Diversity Index (H’) ranged from 0,377 to 1,785, Index Uniformity (E) ranges from 0,234 to 0,772, and the index Dominance (C) ranges between 0214-0851. Principal Component Analysis of phytoplankton abundance correlated positively with nitrate (NO3+), salinity and pH, whreas phospate (PO4+), DO, temparature, brightness and speed of flow showed a negative correlation.